Sarumpun marriage phenomenon: analysis of Islamic law perspective - Yandi, Akmal; Akem, Umar; Dewi, Erna; Netti, Misra; Adrinoviyan, Adrinoviyan (UKAZ: International Journal of Islamic Studies, 2024)
Minangkabau society, which adheres to a matrilineal kinship system, considers marriage as an important event. In Minangkabau custom, sarumpun marriage is strictly prohibited, and violations are subject to customary punishment. However, in Islamic law, there is no prohibition against sarumpun marriage. This study aims to determine the view of Islamic law in the perspective of 'urf on the prohibition of sarumpun marriage. The method used is a qualitative method with an ethnographic approach with data sources from interviews, observations with traditional leaders and data from related books and articles. The results show that Minangkabau custom prohibits sarumpun marriage, but still considers it valid. In Islam, this marriage is not haram, but makruh. From the perspective of urf, this prohibition is included in the valid urf, because Imam Ghazali stated that sarumpun marriage is makruh. In addition, Islam recommends avoiding marriage with close relatives because it can produce weak offspring, as the opinion of the jurists is that a person's lust tends to be weak towards close relatives.